2013
DOI: 10.1093/ajh/hpt158
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Aliskiren/Amlodipine Combination and High-Dose Amlodipine Monotherapy on Endothelial Function in Elderly Hypertensive Patients

Abstract: UMIN000010163.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The fact that some of our patients had different profiles of cardiovascular risk factors and use of cardiovascular drugs, in addition to psoriasis and its treatment, which could influence RHI indexes, could be regarded as a lack of control. [45][46][47] However, evaluating EF before and after antipsoriatic therapy in the same patients with the same risk factors and the same use of cardiovascular drugs, and the fact that patients who were treated with cardiovascular drugs presented similar tendencies (Tables 2 and 3), gave us the confidence that the role of antipsoriatic therapy could be isolated.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that some of our patients had different profiles of cardiovascular risk factors and use of cardiovascular drugs, in addition to psoriasis and its treatment, which could influence RHI indexes, could be regarded as a lack of control. [45][46][47] However, evaluating EF before and after antipsoriatic therapy in the same patients with the same risk factors and the same use of cardiovascular drugs, and the fact that patients who were treated with cardiovascular drugs presented similar tendencies (Tables 2 and 3), gave us the confidence that the role of antipsoriatic therapy could be isolated.…”
Section: Discussionmentioning
confidence: 99%
“…The AQUARIUS study, which analyzed the effects of the drug in prehypertensive individuals with coronary atherosclerosis, concluded that it did not offer any additional benefit to patients (Nicholls et al, ). However, many studies reported beneficial effects of ALI in regard to endothelial function and arterial rigidity (Bonadei et al, ; Fukutomi, Hoshide, Mizuno, & Kario, ; Raptis et al, ). Furthermore, it reduces ventricular mass according to the ALLAY study, which revealed that ALI is as effective as losartan in the reduction of hypertrophied ventricular mass in hypertensive patients with BMI >25 kg/m 2 (Solomon et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The possible benefits of ALI on other physiological targets, such as endothelial function and arterial stiffness, on which recent studies have suggested favorable effects [108,109,110] warrant further investigation. Also, the exact clinical implications in the role of disease of the (pro)renin receptor and PRA levels should be established, as ALI has an effect on both.…”
Section: Discussionmentioning
confidence: 99%